Pengaruh Reward dan Punishment dalam Meningkatkan Motivasi Belajar di SDN 192 Pekanbaru - Oky Syamsurizal; Miftahir Rizqa; Risnawati Risnawati; Yurifa Aulia Ali (Departement of Mathematics Education, 2025)
This research aims to analyze the effect of applying rewards and punishments in increasing students' learning motivation at SDN 192 Pekanbaru. In the educational context, learning motivation is an important factor that influences student academic achievement. Based on observations, teachers at SDN 192 Pekanbaru have implemented a reward system by giving praise, awards and prizes in the form of stationery to students who successfully complete assignments well. Apart from that, punishment is also implemented when students make mistakes, in the form of punishments such as memorizing short letters. , reducing scores, and cleaning the school yard. The application of these two methods is expected to increase students' attention and participation in the teaching and learning process, as well as encourage them to try harder in learning. The results of the research show that the combination of reward and punishment applied consistently can motivate students to improve their learning achievement. This is in line with Nasution's opinion which states that rewards function as encouragement to study harder, while punishment can correct undesirable behavior. Thus, this research concludes that the application of appropriate rewards and punishment can contribute significantly to increasing student learning motivation at SDN 192 Pekanbaru, as well as providing recommendations for teachers to continue to develop more innovative and effective teaching methods.